1993
DOI: 10.1002/jcp.1041570227
|View full text |Cite
|
Sign up to set email alerts
|

Induction of collagenase and stromelysin gene expression by mechanical injury in a vascular smooth muscle‐derived cell line

Abstract: We describe a novel system for studying the production of matrix metalloproteinases types I and III (collagenase and stromelysin) by a vascular smooth muscle cell line (Rb-1 cells) in response to mechanical injury. Highly confluent Rb-1 cells are disrupted by passing a plastic comb around the plate to clear a series of circumferential paths, which are bordered by two ridges of displaced cells. Over the next 24 hours, cells migrate into the cleared areas. Northern blot analysis demonstrates the accumulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 57 publications
1
50
0
Order By: Relevance
“…fl-coll [3], as well as other signals that induce changes in cell morphology and actin reorganization, stimulate MMP-1 expression. The other signals include mechanical strain [4] and direct mechanical wounding [5] in human vascular smooth-muscle cells, exposure to cytochalasin D in human and rabbit synovial fibroblasts [6,7] and specific cell-matrix interactions [8].…”
Section: Introductionmentioning
confidence: 99%
“…fl-coll [3], as well as other signals that induce changes in cell morphology and actin reorganization, stimulate MMP-1 expression. The other signals include mechanical strain [4] and direct mechanical wounding [5] in human vascular smooth-muscle cells, exposure to cytochalasin D in human and rabbit synovial fibroblasts [6,7] and specific cell-matrix interactions [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a wealth of data supports an important role for SMC migration in the evolution of a neointima, 47,48 and atRA has been shown to suppress SMC migration in vitro, apparently through an inhibition of the AP-1-dependent proteases collagenase and stromelysin. 19 Because there is mounting evidence supporting a critical role for retinoid receptors in modulating such gene expression, 18 an examination of retinoid receptors within the normal and injured vessel wall should be a future goal. Another possible mechanism for atRA-mediated reduced intimal mass may relate to accelerated cell death.…”
Section: Atra and Neointimal Formationmentioning
confidence: 99%
“…15 Many effects elicited by retinoids are of relevance to the pathogenesis of human restenosis. For example, all-trans-retinoic acid (atRA) promotes differentiation 16 and fibrinolysis 17 and inhibits cell proliferation, 18 migration, 19 thrombosis, 20 angiogenesis, 21 platelet aggregation, 22 and inflammation. 23 Although their clinical efficacy has been documented for some proliferative disorders, 24,25 virtually nothing is known with respect to retinoids and vascular occlusive disease.…”
mentioning
confidence: 99%
“…RA has been shown to reduce SMC migration, possibly by decreasing collagenase and stromelysin transcription, 2 MMPs induced by mechanical injury. 84 However, we have observed that RA increases migration of both medial and IT15 SMCs, probably by stimulating tissue-type plasminogen activator (tPA) activity. 28 tPA is the main PA involved in the proteolytic activities of SMCs in vitro, and the higher proteolytic activity of IT15 cells is mainly due to increased expression of tPA.…”
Section: Ra and Smc Biological Featuresmentioning
confidence: 99%